Proposals for Annual Plan (1990-91) of Eighth Five Year Plan (1990-95) of Haryana Agricultural University - Planning Commission (Planning Commission, 1989)
Before giving the details regarding formulation of projection for the year 1990-91, it cells for a critical review of targets -and achievements made/likely to be made during 7th plan period. the food grains production Targets for the 7th plan were projected at 90.00 lakh tonnes, while that of sugarcane (gur), cotton and oilseeds at 8.50 lakh tonnes, 9.50 lakh bales and 2.25 lakh tonnes, respectively.
Planning Department, Government of Haryana